Cervical Cancer Genetic Susceptibility: A Systematic Review and Meta-Analyses of Recent Evidence. - Gabriela A Martínez-Nava; Julián A Fernández-Niño; Vicente Madrid-Marina; Kirvis Torres-Poveda (PLoS ONE)
Introduction Cervical cancer (CC) has one of the highest mortality rates among women worldwide. Several efforts have been made to identify the genetic susceptibility factors underlying CC development. However, only a few polymorphisms have shown consistency among studies. Materials and methods We conducted a systematic review of all recent case-control studies focused on the evaluation of single nucleotide polymorphisms (SNPs) and CC risk, stringently following the "PRISMA" statement recommendations. The MEDLINE data base was used for the search. A total of 100 case-control studies were included in the meta-analysis. Polymorphisms that had more than two reports were meta-analyzed by fixed or random models according to the heterogeneity presented among studies. Results We found significant negative association between the dominant inheritance model of p21 rs1801270 polymorphism (C/A+A/A) and CC (pooled OR = 0.76; 95%CI: 0.63-0.91; p<0.01). We also found a negative association with the rs2048718 BRIP1 polymorphism dominant inheritance model (T/C+C/C) and CC (pooled OR = 0.83; 95%CI: 0.70-0.98; p = 0.03), as well as with the rs11079454 BRIP1 polymorphism recessive inheritance model and CC (pooled OR = 0.79; 95%CI: 0.63-0.99; p = 0.04). Interestingly, we observed a strong tendency of the meta-analyzed studies to be of Asiatic origin (67%). We also found a significant low representation of African populations (4%). Conclusions Our results provide evidence of the negative association of p21 rs1801270 polymorphism, as well as BRIP1 rs2048718 and rs11079454 polymorphisms, with CC risk. This study suggests the urgent need for more replication studies focused on GWAS identified CC susceptibility variants, in order to reveal the most informative genetic susceptibility markers for CC across different populations.